A study of the prevalence of gonadal dysfunction and its association with increasing disease severity in patients diagnosed with chronic kidney disease at a tertiary care center in Kolkata, West Bengal - Parasher, Anant; Ranjan, Kunal; Munjal, Vanshika (International Journal of Research in Medical Sciences, 2021)
Background: Hypergonadotropic hypogonadism is a well described hormonal derangement associated with chronic kidney disease, also known as uremic hypogonadism. The objective of this study was to assess the prevalence of gonadal dysfunction associated with chronic kidney disease and to study the co-relation of gonadal dysfunction with disease severity. Methods: In this cross-sectional observational study, 50 patients with diagnosed chronic kidney disease were included during the one-year period from May 2015 to April 2016. The clinical and biochemical parameters related to gonadal dysfunction were evaluated in these cases. Results: Out of the 28 male CKD patients, 19 (68%) patients had Serum Testosterone values less than 90 ng/dl, 18 (64%) patients had a serum leutinizing hormone (LH) level greater than 9 mIU/ml and 19 (68%) patients had a serum follicle stimulating hormone (FSH) level greater than 13 mIU/ml. Out of 22 female CKD patients, 14 (64%) patients had serum estradiol value less than 50 pg/ml, 12 (54%) patients had Serum LH level greater than 80 mIU/ml and 20 (91%) patients had a S. FSH level greater than 26 mIU/ml. Out of a total of 50 patients in this study, 34 patients showed evidence of gonadal dysfunction, the majority of them belonging to stage 5 CKD. Conclusions: Out of the 34 patients showing gonadal dysfunction, 5 (15%) patients were in stage 3 CKD, 11 (32%) patient were in stage 4 CKD and 18 (53%) were in stage 5 CKD. It may be proposed that gonadal dysfunction is very common in CKD patients and the frequency of sexual dysfunction increases as the renal function deteriorates.